Pelatihan Structural Equation Modeling (SEM) dengan Pendekatan Partial Least Square (PLS) Berbasis R tanpa Koding menggunakan Platform Losari Digital - Hamzah, Muh. Qardawi; Bakri, Rizal; Islamiah, Farida (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
This training aims to address challenges in Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis by introducing Losari Digital, a GUI-based platform that enables analysis without coding. The activity was conducted online via Zoom Meeting on July 5, 2025, and was attended by 105 participants. The training was divided into two sessions: presentation of basic PLS-SEM concepts and hands-on practice using Losari Digital. The success of the training was evaluated through a feedback survey covering aspects of material, media, and content. The results showed that the training was significantly successful. Participants rated the material as clear, the interaction as good, and the audio-visual media as high quality. The content was considered educational, useful, interesting, and informative. The majority of participants agreed or strongly agreed with the overall quality. These findings confirm that the coding-free approach through Losari Digital effectively bridges theory and practice, while reducing technical barriers in the application of advanced data analysis methods.